MENINGKATKAN HASIL BELAJAR MENENDANG BOLA MELALUI PERMAINAN SEPTI PADA SISWA KELAS IV SD NEGERI NGADIRGO 02 KECAMATAN MIJEN KOTA SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Problem encountered in this study is whether learning kicking ball through thegame Septi improves the outcome of fourth grade Elementary School Ngadirgo 02students Mijen Semarang in 2013? While the purpose of this study was todetermine the enhancement of learning kicking ball using the game septi on fourthgrade stu-dents at SDN Ngadirgo 02 subdistrictMijen semarang city Year 2013.Based on the results of this study in the first cycle of 69.43% affective, cognitive66.66% and psychomotor 67.58% and in the second cycle aspect of affective is84.2%, cognitive 82.4% and psychomotor 85.1%, while the level of enthusiasm andthe students’ responses during the learning kicking the ball through the game Septiin the second cycle is very positive.Results: 1) learning to kick a ball through the game septi is more effective in thelearning process of Penjasorkes. 2) student’s enthusiasm during joining learningPenjasorkes kicking the ball through the game Septi is very high and students alsofeel happy, so indirectly, it increasees student activities covering aspects ofaffective, cognitive and psychomotor. Suggestions 1) for teacher, please be morecreative and innovative teachers in the learning process of kicking the ball in thegame of foot-ball. 2) Show lerning motivation in order to improve the learningprocess, because learning is fun.